Efficient OER Catalyst with Low Ir Volume Density Obtained by Homogeneous Deposition of Iridium Oxide Nanoparticles on Macroporous Antimony‐Doped Tin Oxide Support. (25th October 2019) - Böhm, Daniel; Beetz, Michael; Schuster, Maximilian; Peters, Kristina; Hufnagel, Alexander G.; Döblinger, Markus; Böller, Bernhard; Bein, Thomas; Fattakhova‐Rohlfing, Dina
Abstract: A multistep synthesis procedure for the homogeneous coating of a complex porous conductive oxide with small Ir nanoparticles is introduced to obtain a highly active electrocatalyst for water oxidation. At first, inverse opal macroporous Sb doped SnO2 (ATO) microparticles with defined pore size, composition, and open‐porous morphology are synthesized that reach a conductivity of ≈3.6 S cm −1 and are further used as catalyst support. ATO‐supported iridium catalysts with a controlled amount of active material are prepared by solvothermal reduction of an IrO x colloid in the presence of the porous ATO particles, whereby homogeneous coating of the complete outer and inner surface of the particles with nanodispersed metallic Ir is achieved. Thermal oxidation leads to the formation of ATO‐supported IrO2 nanoparticles with a void volume fraction of ≈89% calculated for catalyst thin films based on scanning transmission electron microscope tomography data and microparticle size distribution. A remarkably low Ir bulk density of ≈0.08 g cm −3 for this supported oxide catalyst architecture with 25 wt% Ir is determined. This highly efficient oxygen evolution reaction catalyst reaches a current density of 63 A gIr −1 at an overpotential of 300 mV versus reversible hydrogen electrode, significantly exceeding a commercial TiO2 ‐supported IrO2 reference catalyst under the same measurement conditions. Abstract : Illustration of the solvothermal loading of open porous antimony doped tin oxide microparticles employed as a catalyst support with a thin layer of catalytic highly active IrO2 nanoparticles is shown. Independent control of the microparticle porosity, doping level, as well as of the IrO x precursor‐to‐support ratio allows for the synthesis of an optimized supported oxygen evolution reaction (OER) catalyst with high catalytic activity for the OER.